2022
DOI: 10.26582/k.54.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between reaction time and gaming time in e-sports players

Abstract: E-sports can be defined as an electronic sports form and is growing at a rapid pace worldwide. E-sport requires high-speed reactions during all games. The purpose of this study was to evaluate auditory, visual and aim reaction times in different duration of game playing in e-sport players. Fifty-three participants were assigned into two groups according to their playing time which was either more or less than 14 hours per week. The participants were tested for auditory reaction time with online website at play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Research on e-sport players showed that RT is affected by game playing time. If gamers play longer, the better RT they can have [27]. It is due to the speed of coding visual information into visual short-term memory, and the improvement does seem to depend on the time devoted to gaming [28].…”
Section: Discussionmentioning
confidence: 99%
“…Research on e-sport players showed that RT is affected by game playing time. If gamers play longer, the better RT they can have [27]. It is due to the speed of coding visual information into visual short-term memory, and the improvement does seem to depend on the time devoted to gaming [28].…”
Section: Discussionmentioning
confidence: 99%
“…The Web site has been widely used in scientific research to measure simple cognitive tasks for e-sports players or general gamers. [1] 2.2.1. Sequence memory test.…”
Section: Cognitive Tasksmentioning
confidence: 99%
“…E-sports have been attracting more and more attention, with the number of spectators reaching 495 million and the revenue reaching approximately $1.1 billion in 2020. [ 1 ] According to the International Federation of eSports, eSports is officially accepted as a sport in more than 60 countries. In the 2022 Asian Games in China, eSports will appear as an official sport.…”
Section: Introductionmentioning
confidence: 99%
“…E-sports usually means using electronic equipment as a carrier to participate in games developed by various game developers, compete with each other, and achieve projects similar to traditional competitive competitions such as Go and badminton [1]. In this way, e-sports refers to the use of various electronic devices, such as mobile phones, iPads, PCs, etc., as sports equipment, to carry out mental, physical and other confrontation sports between players [2]. In this sport, if it is a team event, it can greatly cultivate team spirit, or if it is an individual event, it can continuously improve the athletes' various willpower and coordination and control capabilities [3].…”
Section: Introductionmentioning
confidence: 99%